A new method for synthesis of carbon nanoparticle and its applications. Issue 1 (31st December 2022) - Kariper, İshak Afşin and Hepokur, Ceylan and Danışman-Kalındemirtaş, Ferdane and Kuruca, Serap Erdem
ABSTRACT: In the present study, we synthesized carbon nanoparticles with a different method using chitosan, a natural polymer. As a result, carbon nanomaterials were diffused directly through the intestinal membrane, and carbon nanoparticles were obtained. Surface and chemical characterizations of the obtained carbon nanoparticles were determined by different techniques such as FTIR, DLS, SEM, EDX, and UV-visible. Moreover, the cytotoxic effects of the carbon nanoparticles on Saos-2, MCF-7 cancer cells, and HUVEC non-cancerous cells were evaluated with the MTT test. Although the size of these carbon nanoparticles is not as small as carbon nanodots, these nanoparticles were very effective on cancer cells. Interestingly, our results showed that drug-free carbon nanoparticles were remarkably cytotoxic on MCF-7 and Saos-2 cancer cells. In addition, 5FU loaded carbon nanoparticles (IC50: 12 µg/mL) were 3.5 times more effective than 5FU alone (IC50: 43 µg/mL) on MCF-7 cell lines. GRAPHICAL ABSTRACT: UF0001